2013
DOI: 10.1089/ars.2012.5015
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Significance of Perioperative Release of Macrophage Migration Inhibitory Factor in Cardiac Surgery?

Abstract: Cardiac surgery is associated with release of the pleiotropic cytokine macrophage migration inhibitory factor (MIF). The trigger for MIF release has not yet been elucidated. Owing to its intrinsic antioxidative activity, MIF might reduce oxidative stress and protect from myocardial ischemia and reperfusion (I/R) injury. In the present study, patients scheduled for elective cardiac surgery (n = 46) were randomized to undergo coronary artery bypass grafting either conventionally with cardiopulmonary bypass and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 10 publications
3
46
1
Order By: Relevance
“…Regarding the clinical relevance of the present findings, several studies have demonstrated that MIF/MIF-2/D-DT act as early stress regulating cytokines in the inflammatory response of patients with myocardial I/R, which often is associated with acute kidney injury (68,71). Autophagy is activated in myocardial I/R injury (47), which, together with the above findings, raises the question of whether elevated blood levels of MIF/MIF-2/D-DT occur in a concentration range that modulates autophagic activity in a beneficial manner.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the clinical relevance of the present findings, several studies have demonstrated that MIF/MIF-2/D-DT act as early stress regulating cytokines in the inflammatory response of patients with myocardial I/R, which often is associated with acute kidney injury (68,71). Autophagy is activated in myocardial I/R injury (47), which, together with the above findings, raises the question of whether elevated blood levels of MIF/MIF-2/D-DT occur in a concentration range that modulates autophagic activity in a beneficial manner.…”
Section: Discussionmentioning
confidence: 60%
“…These increased MIF concentrations could stimulate the release of proinflammatory cytokines such as tumor necrosis factor α, IL‐1β, and IL‐6, which have been linked to the development of AKI . In contrast, Stoppe et al reported that the perioperative release of MIF was associated with enhanced antioxidant activity and a reduced postoperative incidence of AKI in patients undergoing cardiac surgery. The authors further discussed a potentially protective role of MIF for kidney function, especially in the context of ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not observe any differences in serum MIF levels between control and RIPC treated patient after RIPC, supporting the other observations of no effects of RIPC. It should be noted however, that many values (25) were below the detection limit, and lower than observed in other studies with CABG patients [47, 48]. Therefore, these results should be interpreted with care.…”
Section: Discussionmentioning
confidence: 63%
“…Ischemia caused a release of MIF from the heart, which has been shown to be cardioprotective by regulation of AMPK signaling, inhibition of pro-apoptotic cascades and reducing oxidative stress [4547]. In CABG patients a perioperative increase in MIF was associated with enhanced antioxidant capacity and reduced organ dysfunction after cardiac surgery [47, 48]. We hypothesized that RIPC can increase MIF.…”
Section: Discussionmentioning
confidence: 99%